Articulation and implementation of professional standards for teachers in teacher education institutions - Bacus, Remedios C.; Tagalog, Rita May P. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2023)
This study determined the constructions of administrators and teachers in the articulation and implementation of the Philippine Professional Standards for Teachers (PPST) in teacher education institutions. A qualitative descriptive approach was employed to explore the narratives of the 20 purposively selected participants from the five higher education institutions in Cebu. Coding and categorization of participants’ vignettes, following Clarke and Braun’s (2014) thematic analysis model, resulted in five indexed themes: neediness not readiness, tenacity, and supportability, challenged but not frustrated, receptivity and positivity, and responsibility and accountability. Points of convergence and divergence were also identified from the TEIs articulation and implementation of PPST. The rationalization attached to integrating the beginning teacher indicators in the teacher education curriculum provides input on establishing contextualized, professional development initiatives for teacher quality. As such, forging partnerships between and among teacher education institutions through curriculum quality audits may be considered.